Wpływ niepewności na efektywność procesów innowacyjnych - Czupiał, Jerzy (The Influence of Uncertainly on the Efficiency of Innovative Processes, 2006)
It is becoming clear that product innovation is a complex process. In this paper the uncertainty of innovation I divided into two separate dimensions: uncertainty about ends and uncertainty about means. This framework, based on the two dimensions, helps to analyse the uncertainty of different kinds of innovations and their management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 262-270